Design and analysis of optical encryption for optical transport networks with a rate of 100Gbps based on Mach–Zehnder interferometers - Amir Khalili; Kambiz Abedi (Scientific Reports)
Abstract This paper proposes a novel MZI (Mach–Zehnder Interferometer) structure for high-speed optical encryption in Optical Transmission Networks (OTNs) operating at 100 Gbps with OTU4 signaling on a silicon-based optical fiber substrate. The design achieves a significantly lower $${V}_{π }l$$ (half-wave voltage length) compared to existing MZIs by engineering the material profile of the MZI arm cladding. Additionally, it introduces a novel approach by utilizing the dispersive arm for precise control of reflecting power. This optimized MZI exhibits a $${V}_{π }l$$ of approximately 13.5 V mm and a bandwidth of 116.5 GHz, resulting in a figure of merit (FOM) of 8.630 GHz/V mm. This represents an 86% improvement over comparable MZI designs, highlighting the significant performance enhancement. Furthermore, the proposed MZI boasts the smallest footprint among similar implementations. Notably, the entire structure, including the synchronizer and switch, leverages the MZI principle. This MZI-based design holds promise for efficient and compact optical encryption in 100 Gbps OTNs.